AN ETNOGRAPHIC CASE STUDY IN EDUCATIONAL RESEARCH - Butvilas, Tomas; Zygmantas, Janete (Acta Paedagogica Vilnensia, 2011)
The authors present an analysis and description of one of the most unique social research strategies – a case study approach to education science and practice. Using Zygmantas’ recent work inn which an ethnographic case study was implemented, along with Yin’s and Stake’s constructivist ideology while grounding a case research design, the main principles, phases, and methodology are discussed. Even though the case study research was mainly based on the areas of economy, law and business, the education field is open also for implementing such a research strategy and as the didactic approach. An example of a case study research in education is presented in the 3rd chapter of this paper revealing obvious strengths and advantages of such a thorough investigation of social phenomena.